Gambaran Life Style Penderita Hipertensi di Puskesmas Olak Kemang Kota Jambi - Kadri, Hasyim (3031-8572, 2024)
Hypertension is a health problem that is quite dangerous throughout the world, because hypertension is a disease that occurs due to problems that often arise from changes in a person's lifestyle or eating patterns, such as consuming foods that are high in salt, high in calories, high in fat, low in fiber, high in stress. experienced, obesity, smoking habits, not consuming enough fruit, lack of physical activity and drinking alcohol will trigger the emergence of hypertension. The aim of the research is to describe the life style of hypertension sufferers at the Olak Kemang Community Health Center, Jambi City. This research is a descriptive research study that was conducted at the Olak Kemang Community Health Center, Jambi City from September 2023 to August 2024. Samples were taken using accidental sampling, the sample size was 95 respondents. Data collection using questionnaires. Research results: Good Lifestyle Description of 56 Respondents. In conclusion, the results of this research can be used to improve the quality of nursing staff services in increasing knowledge of the lifestyle of hypertension sufferers to the public using various media such as social media leaflets